Suspension of Sonchus arvensis L Leaves Ethanolic Extract Affects Blood Creatinine and Urea Levels in Streptozotocin-Induced Wistar Male Rats - Dewi, Niluh Puspita; Alaydrus, Syafika; Lestari, Widya Ayu; Magfirah, Magfirah; Utami, Indah Kurnia; Polontalo, Nani Astria; Tuldjanah, Muthmainah (Sciences of Pharmacy, 2024)
The study focused on analyzing the secondary metabolites present in the ethanol extract of Sonchus arvensis L. leaves (SALEE) and their impact on creatinine and urea levels when administered in suspension form at different doses. Phytochemical screening of SALEE identified alkaloids, flavonoids, phenols, saponins, and tannins. In the experiment, twenty-five white male rats were divided into five groups: a healthy control group (Group I), a negative control group (Group II), and three test groups (Groups III, IV, and V) receiving SALEE at doses of 200, 300, and 400 mg/kg BW, respectively. After inducing diabetes with streptozotocin and a 21-day follow-up period, creatinine and urea levels were assessed. The results demonstrated that SALEE administration significantly reduced creatinine levels and increased urea levels. Notably, the 200 mg/kg BW dose of SALEE exhibited a consistent and long-term effect. It was observed that blood urea levels fluctuated even in healthy and negative control groups during the 21-day observation period. In the group receiving the highest dose of SALEE (400 mg/kg BW), blood urea levels increased significantly on days 14 and 21, indicating a potential increase in the rats' appetite rather than renal function failure. Overall, the findings suggest that SALEE has promising potential to regulate creatinine and urea levels in the blood of individuals with diabetes, highlighting its potential for therapeutic and supplemental use.